PERANCANGAN ALAT MONITORING TEGANGAN DAN ARUS LISTRIK BERBASIS MIKROKONTROLER ARDUINO UNTUK RUMAH - Erick Radwitya; Syarif Ishak Alkadri (JURNAL SIMETRIK, 2026)
The increasing household electricity consumption drives the need for effective monitoring systems to optimize energy usage and enhance electrical installation safety. This research develops a prototype monitoring device based on an Arduino Mega 2560 microcontroller, integrated with a ZMPT101B voltage sensor and an ACS712-30A current sensor, to measure electrical parameters in real time. The research methodology employs a quantitative experimental approach with stages including hardware design, firmware development, sensor calibration, and accuracy validation using standard measuring instruments. The system features a 20x4 LCD interface for local display and an ESP8266 module for transmitting data to the Blynk platform, enabling remote monitoring via a mobile application. Testing results demonstrate excellent accuracy, with Mean Absolute Percentage Errors of 0.69% for voltage, 1.66% for current, and 1.76% for active power. System response time reaches 87 milliseconds with data transmission latency of 1.45 seconds, meeting real-time monitoring standards. The notification system successfully detects overvoltage and overcurrent conditions with 99% reliability and an average response time of 92 milliseconds. Testing across various load types shows optimal performance at a power factor above 0.85. This system offers a cost-effective solution to improve energy efficiency and the safety of household electrical installations, with an affordable implementation cost. Keywords: ACS712 sensor, Arduino, Energy Monitoring, Internet of Things, ZMPT101B sensor